2011
DOI: 10.1002/mnfr.201100392
|View full text |Cite
|
Sign up to set email alerts
|

Beneficial effects of mangiferin on hyperlipidemia in high‐fat‐fed hamsters

Abstract: The results suggest that mangiferin may ameliorate hypertriglyceridemia partly by modulating the expression levels of genes involved in lipid oxidation and lipogenesis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
75
0
1

Year Published

2013
2013
2016
2016

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 97 publications
(87 citation statements)
references
References 42 publications
11
75
0
1
Order By: Relevance
“…Mangiferin (50-150 mg/kg per day) has been demonstrated to have an effect on excessive hepatic triglyceride accumulation in high fat diet-fed hamsters (Guo et al, 2011) and Wistar rats (Niu et al, 2012), similar to that in WKY and SHR in the present study. However, the antisteatotic effect was accompanied by augmentation of high fat diet-stimulated overexpression of both hepatic and muscular CD36 mRNA in hamsters (Guo et al, 2011).…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Mangiferin (50-150 mg/kg per day) has been demonstrated to have an effect on excessive hepatic triglyceride accumulation in high fat diet-fed hamsters (Guo et al, 2011) and Wistar rats (Niu et al, 2012), similar to that in WKY and SHR in the present study. However, the antisteatotic effect was accompanied by augmentation of high fat diet-stimulated overexpression of both hepatic and muscular CD36 mRNA in hamsters (Guo et al, 2011).…”
Section: Discussionsupporting
confidence: 84%
“…However, the underlying mechanisms of action are still largely unknown. We and others have reported that they improve numerous lipid metabolism-associated abnormalities, such as fatty liver, hyperlipidemia, excessive cardiac lipid accumulation and obesity (Huang et al, 2006a,b;Guo et al, 2011;Niu et al, 2012;Liu et al, 2013;Xing et al, 2014;Na et al, 2015). We hypothesized that regulation of lipid metabolism might be associated with the antidiabetic property of mangiferin.…”
Section: Introductionmentioning
confidence: 92%
“…Similar effects of mangiferin in improving dyslipidemia were previously reported in streptozotocin diabetic rats (Guo et al 2011, Muruganandan et al 2005. Mangiferin may mediate its action on lipid profile through increasing fatty acid uptake in the liver via upregulation of the expression of fatty acid translocase (Guo et al 2011), downregulation of microsomal triglyceride transfer protein (MTP) and upregulation of hepatic PPAR-α expression (Guo et al 2011).…”
Section: Discussionmentioning
confidence: 59%
“…Similar effects of mangiferin in improving dyslipidemia were previously reported in streptozotocin diabetic rats (Guo et al 2011, Muruganandan et al 2005. Mangiferin may mediate its action on lipid profile through increasing fatty acid uptake in the liver via upregulation of the expression of fatty acid translocase (Guo et al 2011), downregulation of microsomal triglyceride transfer protein (MTP) and upregulation of hepatic PPAR-α expression (Guo et al 2011). According to the Randle's glucose-fatty acid cycle, increased plasma triglycerides and increased free fatty acid (FFA) oxidation impairs insulin action, glucose metabolism and utilization leading to hyperglycemia and consequently, reduction of triglycerides could participate to the hypoglycemic effect of mangiferin (Randle et al 1963).…”
Section: Discussionmentioning
confidence: 59%
“…Alternatively HL can be induced by dietary means (e.g. chronic feeding of a high fat diet) (11,13,40,43) or by treatment with compounds such as Triton (14,26) or poloxamer 407 (P407) (16). P407, a non-ionic synthetic copolymer surfactant, provides an attractive means of inducing HL because of its rapid onset and seeming lack of overt toxicity; within 24 h of its intraperitoneal (i.p.)…”
Section: Introductionmentioning
confidence: 99%